Uniportal video-assisted thoracic surgery: twentieth anniversary - Migliore, Marcello (Journal of Thoracic Disease, 2018)
After 2 years, while reading the editorial entitled “Fact checking in the history of uniportal video-assisted thoracoscopic surgery” (1), an attempt to undermine the work done with tremendous sacrifice by myself and team has been noted; and therefore, as silence implies consent, but also it could be exchanged as arrogance and superiority, the reply to the editorial, step by step using particular attention to find details in the body of scientific evidence, is mandatory.